Interpersonal skills for the negotiation by the lifestyle and occupational level in industry production of Peru - Paredes Tarazona, Mildred (2011)
This raises interpersonal skills for negotiation differ between Lifestyle and Occupational levels of actors in production companies, in Lima, Peru? The population intentional, consisting of stable workers who perform the four occupational levels of four private companies producing in Peru in Lima, Peru. Applied investigation non-experimental and descriptive cross-sectional comparative study on data collected with the Questionnaire for the Negotiation Skills (CHNC-2008), validity of 0.85 and the Inventory Monofactorial Lifestyle, validity of  0.90, as revised and reduced (2006) for the study, written by Vicuña, Luis and Hernández, Héctor. The Kruskal Wallis and Mann Whitney U was applied for intergroup comparison, the significance level no greater than 0.05 in the testing of the hypothesis by the not normal distribution of data from the Skills for the negotiation of conflicts for each one of four Lifestyle and four levels in employment. Conclusion: Interpersonal skills for negotiation differs significantly depending on the acquired lifestyles and occupational level of the population of manufacturing companies in Peru